The impact of core training on overall athletic performance in different sports: a comprehensive meta-analysis - Tongwu Yu; Yuxiong Xu; Zijian Zhang; Yongsheng Sun; Jinghui Zhong; Chuanwei Ding (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background and objectives Despite widespread implementation of core training in athletic preparation, evidence regarding its effectiveness across different sports and performance domains remains fragmented. This meta-analysis examined the effects of core training on athletic performance across multiple sports, addressing limitations of previous analyses that focused on single sports or limited performance measures. Methods Following PRISMA guidelines, we conducted a systematic review across five databases (PubMed, Web of Science, Scopus, SPORTDiscus, and Google Scholar). We assessed methodological quality using the PEDro scale and risk of bias using the Cochrane tool. Eligibility criteria included randomized controlled trials published between 2014–2024 involving healthy athletes aged 15–25 years, with core training as the primary intervention. Results From an initial 1,670 records identified, 29 studies met rigorous inclusion criteria, comprising 956 athletes aged 15–23 years. Core training demonstrated significant improvements in general athletic performance (SMD = 1.38, 95% CI [0.85, 1.82], p < 0.001), with notably strong effects on core endurance (SMD = 1.32, 95% CI [0.57, 2.08], p < 0.004) and balance (SMD = 0.99, 95% CI [0.29, 1.69], p = 0.01). Core training revealed a moderate but insignificant effects on sport-specific performance (SMD = 0.62, 95% CI [-0.08, 1.31], p = 0.084). The analysis revealed non-significant effects sport-specific outcomes: speed (SMD = -0.28 [-0.86, 0.31], p = 0.28); maximal strength (SMD = 7.57 [-7.75, 22.89], p = 0.27); flexibility (SMD = 0.48 [-0.76, 1.73], p = 0.3); change of direction (SMD = 0.10 [-0.56, 0.76], p = 0.69); technical skill performance (SMD = 0.71 [-4.38, 5.81], p = 0.75); throwing velocity/distance (SMD = 1.52 [-0.43, 3.48], p = 0.1) and vertical jump height (SMD = 0.90 [-0.23, 2.03], p = 0.1). The high heterogeneity across outcomes (I2 = 37–100%) indicates that training responses vary substantially depending on competitive level, intervention duration, and sport-specific contexts, suggesting the need for carefully tailored core training approaches. Conclusion This analysis demonstrates that core training effectively improves foundational athletic qualities but shows variable effects on sport-specific performance measures. The findings suggest core training should be integrated with sport-specific training for optimal performance enhancement. Future research should address the high heterogeneity observed by implementing standardized protocols and examining long-term training effects.